Metabolomic Fingerprinting of Salinispora From Atlantic Oceanic Islands - Bauermeister, Anelize; Velasco-Alzate, Karen; Dias, Tiago; Macedo, Helena; Ferreira, Elthon G.; Jimenez, Paula C.; Lotufo, Tito M. C.; Lopes, Norberto P.; Gaudêncio, Susana P.; Costa-Lotufo, Letícia V. (Frontiers in Microbiology, 2018)
Salinispora (Micromonosporaceae) is an obligate marine bacterium genus consisting of three species that share over 99% 16S rRNA identity. The genome and biosynthetic pathways of the members of this genus have been widely investigated due to their production of species-specific metabolites. However, despite the species’ high genetic similarity, site-specific secondary metabolic gene clusters have been found in Salinispora strains collected at different locations. Therefore, exploring the metabolic expression of Salinispora recovered from different sites may furnish insights into their environmental adaptation or their chemical communication and, further, may lead to the discovery of new natural products. We describe the first occurrence of Salinispora strains in sediments from the Saint Peter and Saint Paul Archipelago (a collection of islets in Brazil) in the Atlantic Ocean, and we investigate the metabolic profiles of these strains by employing mass-spectrometry-based metabolomic approaches, including molecular networking from the Global Natural Products Social Molecular Networking platform. Furthermore, we analyze data from Salinispora strains recovered from sediments from the Madeira Archipelago (Portugal, Macaronesia) in order to provide a wider metabolomic investigation of Salinispora strains from the Atlantic Oceanic islands. Overall, our study evidences a broader geographic influence on the secondary metabolism of Salinispora than was previously proposed. Still, some biosynthetic gene clusters, such as those corresponding to typical chemical signatures of S. arenicola, like saliniketals and rifamycins, are highly conserved among the assessed strains.